دور استراتيجيات تنمية الموارد البشرية في تحسين مستوى الأداء التدريسي و البحثي للأستاذ الجامعي ( دراسة استطلاعية في كلية العلوم الاقتصادية والتجارية وعلوم التسيير بجامعة الشلف) - زروخي, فيروز; مخزومي, لطفي; ختيري, وهيبة (جامعة الوادي - University of Eloued, 2019)
هدفت الدراسة إلى إبراز دور استراتيجيات تنمية الموارد البشرية ممثلة في ( استراتيجية التدريب، التعلم التنظيمي، تطوير المسار الوظيفي، تدعيم السلوك الإبداعي) في تحسين مستوى أداء الأستاذ الجامعي، و للإشارة فقد ركزنا على الأداء البحثي و الأداء التدريسي و ذلك بالتطبيق على عينة من أساتذة كلية العلوم الاقتصادية و التجارية و علوم التسيير بجامعة الشلف، حيث وزعنا 60 استمارة استبيان، كانت 47 استمارة منها صالحة للمعالجة الإحصائية. خلصت الدراسة إلى أن متوسط استجابات أفراد عينة الدراسة لاستراتيجيات تنمية الموارد البشرية المعتمدة بالكلية محل الدراسة جاءت متوسطة، أما تقييمهم لمستوى أداءهم فقد جاء بنسبة مرتفعة، كما توصلت الدراسة كذلك إلى أنه توجد علاقة ارتباط موجبة بين متغيري الدراسة إلا أن القوة التفسيرية كانت ضعيفة جدا. The study aimed to highlight the role of human resource development strategies represented in (training strategy, organizational learning, career development, and reinforcement of creative behavior) in improving the performance of the university professor, and to focus on the research performance and teaching performance by applying to a sample of professors Faculty of Economic, Commercial and Management Sciences at the University of Chlef, where we distributed 60 questionnaire forms, of which 47 were valid for statistical processing.The study concluded that the average responses of the sample of the human resources development strategies approved by the college in question were medium. Their evaluation of their performance level was high. The study also found that there was a positive correlation between the two variables, but the explanatory force was very weak.
The Role of Human Resources Development Strategies in Improving Teaching and Research Performance of the University Professor (Exploratory Study at the Faculty of Economic, Commercial and Management Sciences, University of Chlef)
مقال
Keywords: تدريب ; تعلم تنظيمي ; تط ; تطوير المسار الوظيفي ; سلوك ابداعي ; أستاذ جامعي ; جامعة الشلف